(3GdYdb GdKejf hGdLhgQ GdfajS GdeNdU ef YjhH GdRja hGdZT hGdJOdjSs - (3SjOj Hf GdeNJGQ Hf GdgjH GdGHjQj,J (B1283 (3g` s ((3GdUGOb Hf eMeO s)
(3ChdgG (B:s
(3GdMeO ddg efRd GdQMeI , heajV GdfYeI , HYO GdbfhW hCTJOGO GdCReI gPG hdjcf ai cQje Ydec hSdje Phbc hagec , CjgG GdCN GdQTjO hGdeQjO Gd MejO Cf GdJbhi gi QCS cd hLeGY cd NjQ hfYeI s
(3BNQgG (B:s
(3GdQGHY , hge GdCYdhf, WGFaI EPG XdehG QMehG ef Xdege , aEf MUd dge EfJbGe ef BOGge cGf HYfGjI ef Gddg JYGdi hMeGjI dMeGg , Ke dJYde CjgG GdCNQ GdQTjO CfG bO CPfG dc ai ESJYeGd eG gh eQShe YfOi , heG YSGc JYKQ Ydjg ai cJH eTGjNfG hGYs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ ajgG HGdMeQIs
(3fSNI JGeI eUMMI s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJUha hGdBOGH GdTQYjIs